Mindfulness-Based Stress Reduction for Posttraumatic Stress Symptoms - Rachel E. Goldsmith PhD; James I. Gerhart PhD; Samantha A. Chesney PhD; John W. Burns PhD; Brighid Kleinman PhD; Megan M. Hood PhD (SAGE Publishing, 2014)
Mindfulness-based psychotherapies are associated with reductions in depression and anxiety. However, few studies address whether mindfulness-based approaches may benefit individuals with posttraumatic stress symptoms. The current pilot study explored whether group mindfulness-based stress reduction therapy reduced posttraumatic stress symptoms, depression, and negative trauma-related appraisals in 9 adult participants who reported trauma exposure and posttraumatic stress or depression. Participants completed 8 sessions of mindfulness-based stress reduction treatment, as well as pretreatment, midtreatment, and posttreatment assessments of psychological symptoms, acceptance of emotional experiences, and trauma appraisals. Posttraumatic stress symptoms, depression, and shame-based trauma appraisals were reduced over the 8-week period, whereas acceptance of emotional experiences increased. Participants' self-reported amount of weekly mindfulness practice was related to increased acceptance of emotional experiences from pretreatment to posttreatment. Results support the utility of mindfulness-based therapies for posttraumatic stress symptoms and reinforce studies that highlight reducing shame and increasing acceptance as important elements of recovery from trauma.